Polycyclic Aromatic Hydrocarbons in Soil and Human Health Risk Levels for Various Land-Use Areas in Ulsan, South Korea - Roy, Debananda; Jung, Woosik; Kim, Jayun; Lee, Minjoo; Park, Joonhong (Frontiers in Environmental Science, 2022)
Multiplicity and complexity in sources account for polycyclic aromatic hydrocarbons (PAHs) in soil and health risk levels in industrial zones. In the present study, cancer risks (CR) for soil-bound carcinogenic PAHs were estimated and compared for the first time in seven different land-use areas adjacent to an industrial zone (Ulsan) in Korea. The entire study area has been recognized as a “low CR” zone (10-6< value <10-4). Hence, all land-use areas were found to have significant (>10-6) CR levels, except for an area used to store ore and iron scraps. Estimated CR levels were highest in the railroad area (RA) and traffic area (TA), followed by those in the industrial area (IA). In addition, exposure through dermal absorption (61–70%) and ingestion (21–39%) were the most common factors for CR levels in the study area. Among all health parameters, exposure duration, body weight, and open skin surface area were distinguished as most sensitive to total CR levels. Moreover, among all carcinogenic PAHs, Indeno[1,2,3-c,d]pyrene and Benzo[a]pyrenewere most sensitive to CR levels. Creosote, which was utilized in railroad ties in RA and vehicular exhaust emission in TA, was classified as a source of soil-bound carcinogenic PAHs. Therefore, CR levels resulting from transportation activities were found to be two to three times higher than those obtained from industrial processes. Transportation activities in urban areas mostly serve to provide rapid and comfortable carriage for commuters. However, these facilities were mostly responsible for potential carcinogen exposure. This study directly challenges the conventional perception that industrial zones are the most polluted areas, especially when compared to transportation zones in urban areas. These findings can help local and national governments to better manage resources and maintain an economic balance.